2020
DOI: 10.3390/sym12050781
|View full text |Cite
|
Sign up to set email alerts
|

ACO Based Variable Least Significant Bits Data Hiding in Edges Using IDIBS Algorithm

Abstract: This work presents a double asymmetric data hiding technique. The first asymmetry is created by hiding secret data in the complex region of the cover image and keep the smooth region unaffected. Then another asymmetry is developed by hiding a different number of secret bits in the various pixels of the complex region. The proposed technique uses the ant colony optimization (ACO) based technique for the classification of complex and smooth region pixels. Then, the variable least significant bits (VLSB) data hid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It combines the fast global search of GA and the efficient search of an optimal solution of ACO. Computer simulation results showed that the proposed scheme substantially improves the round robin and ACO algorithms in terms of the rate of search for an optimal path, round trip time, and packet loss rate [36]. Tab.…”
Section: Comparison With Past Studiesmentioning
confidence: 98%
“…It combines the fast global search of GA and the efficient search of an optimal solution of ACO. Computer simulation results showed that the proposed scheme substantially improves the round robin and ACO algorithms in terms of the rate of search for an optimal path, round trip time, and packet loss rate [36]. Tab.…”
Section: Comparison With Past Studiesmentioning
confidence: 98%